(untitled) (Al-Qamar, 2025)
Education is one of the most significant pillars of human civilization and social development. It not only imparts knowledge but also cultivates values, morality, and a constructive approach towards life. This research explores the concept and importance of education in the light of Qur’anic teachings and social realities. The Qur’an, as the primary source of guidance, emphasizes knowledge as the foundation of human dignity and success, beginning with the command of "Iqra" (Read). It highlights the transformative power of education in eliminating ignorance, shaping ethical behavior, and developing a just society. Education in the Islamic framework is not limited to the acquisition of information but extends to the nurturing of intellect, spirituality, and character. Furthermore, the study analyzes the role of education in contemporary society, where challenges such as materialism, moral decline, and social disintegration demand a revival of Qur’anic guidance. The paper also examines how education strengthens social structures by fostering tolerance, cooperation, and awareness among individuals. The discussion reveals that education is both a divine command and a social necessity that bridges the gap between tradition and modernity. In conclusion, education must be redefined beyond formal schooling and considered as a lifelong process that integrates personal growth with social progress. The findings of this study call for reorientation of educational policies and practices according to Qur’anic principles to ensure the holistic development of individuals and societies.